2016
DOI: 10.1007/s11356-016-6045-2
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and health risk assessment of metal(loid)s in indoor dust from two typical cities of China

Abstract: Eleven trace metal(loid)s were determined in the household dust samples from Chengdu and Tianjin, China, and related human exposure and health risk to metal(loid)s via indoor dust intake were evaluated. The trace metal(loid)s were found to be highly concentrated and polluted in the indoor environment of Chengdu and Tianjin, especially for Cu, Zn, Cd, Sb, and Pb, of which the enrichment factors exceeding 5. Metal(loid) levels in the indoor dust samples exhibited no statistical differences between the two cities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…As the result showed, the HQ dermal contact of Cr determined for more than 63% of HI dermal contact for children. This was consistent with the previous studies; they reported that dermal contact with Cr contributed to higher non-carcinogenic risk compared to other exposure routes [17, 40].…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…As the result showed, the HQ dermal contact of Cr determined for more than 63% of HI dermal contact for children. This was consistent with the previous studies; they reported that dermal contact with Cr contributed to higher non-carcinogenic risk compared to other exposure routes [17, 40].…”
Section: Resultssupporting
confidence: 93%
“…Notably, the Cr 6+ is much more toxic than Cr 3+ and other metals that were used to assess human exposure in this study. However, Cr 6+ is decreased into Cr 3+ in the human body; thus, there might be an overestimation in determining health risk [17, 41]. It should be noted that the HI total elements (HQ ingestion + HQ dermal contact ) values for children were higher than that of an adult, suggesting that children were more susceptible to non-carcinogenic risk from the heavy metals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general information of 30 eligible papers focused on 13 types of metals in household dust was shown in Table 1 12,17–19,21,29–53 . Twenty‐one papers were conducted in rural areas, while 17 papers were conducted in urban areas.…”
Section: Resultsmentioning
confidence: 99%
“…The high temperature promotes efficiently the decomposition of HCOOH into active H 2 , which can reduce Cr (VI) directly. Besides, the increase of temperature is beneficial to the increase of acidity on the surface of the catalyst, [41] which further accelerates the reaction. However, reaction at high temperature is not easy to operate or energy-efficient.…”
Section: Resultsmentioning
confidence: 99%